2002
DOI: 10.1055/s-2002-20048
|View full text |Cite
|
Sign up to set email alerts
|

Iridoids with Anti-Inflammatory Activity from Vitex peduncularis

Abstract: A new iridoid, pedunculariside, together with the known iridoid agnuside were isolated from the butanol extract of Vitex peduncularis stem bark. Both pedunculariside and agnuside showed preferential inhibition of COX-2, with IC50 values of 0.15 +/- 0.21 mg/ml and 0.026 +/- 0.015 mg/ml respectively, while having only small inhibitory effects on COX-1. Both compounds did not exhibit cytotoxicity against vero cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 3 publications
0
32
0
1
Order By: Relevance
“…28) However, iridoid compounds 2-4 did not inhibit platelet aggregation, indicating a different inhibition mechanism on the BF decrease. There have been many reports on the anti-allergic effects of iridoid derivatives which inhibit the production of COX-2 29) or NO, 30) or the expression of iNOS and COX-2. 31) Inhibition of the BF decrease by iridoid derivatives may occur in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…28) However, iridoid compounds 2-4 did not inhibit platelet aggregation, indicating a different inhibition mechanism on the BF decrease. There have been many reports on the anti-allergic effects of iridoid derivatives which inhibit the production of COX-2 29) or NO, 30) or the expression of iNOS and COX-2. 31) Inhibition of the BF decrease by iridoid derivatives may occur in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…It was not toxic to vero cells (IC 50 Ͼ50 mg/ml). 109) As this iridoid, 224 contains a C-5 hydroxy group, possibly it is the structural requirement for an iridoid to exhibit anti HSV-1 activity.…”
Section: (Z)-mentioning
confidence: 99%
“…8) No phytochemical study of this plant has been reported so far. In our search for biologically active substances of new structural types from Thai natural resources, [9][10][11][12] we investigated the chemical constituents and biological activities of this plant species and have found that the ethyl acetate extract of the root bark of Z. cambodiana showed pronounced in vitro antimalarial potential against Plasmodium falciparum. In this paper, we report the isolation and characterization of a new tritrpene ester (1), together with five known lupane constituents: lupeol (2), 13) betulinaldehyde (3), 14) the major metabolite betulinic acid (4), 13) 2-O-E-p-coumaroylalphitolic acid (5), 1) and alphitolic acid (6), 1) and three ceanothane triperpenes: zizyberanalic acid (7), 15) zizyberenalic acid (8) 15) and ceanothic acid (9), 16) as the antiplasmodial and antituberculosis constituents of the root bark of this plant species.…”
mentioning
confidence: 99%